Pengaruh PDRB, Jumlah Penduduk dan Pengangguran terhadap Kemiskinan di Kota Banjarmasin - Septiana; Rusdiansyah (PPJP ULM, 2019)
This research to find out about the influence of PDRB, population, and unemployment to poverty in Banjarmasin city year 2002-2016. Poverty is a problem that has not been resolved to date, even though several government efforts have been made to reduce poverty. In this study, we can see how big the poverty level and which factors affect poverty so that we can find solutions and policies appropriate to overcome poverty in the city of Banjarmasin. The scope of this study covers poverty conditions in Banjarmasin using time series data by analyzing for 15 years. The method of analysis used is the multiple linear regression analysis methods. By using the R-Square Test (R2), Simultaneous Test (F Test), and Individual Test (t-test). The research on the influence of PDRB, population, and unemployment together affects poverty. PDB and unemployment have no significant effect on poverty. While the number of residents significantly influence the poverty in the city of Banjarmasin. The most dominant factor affecting poverty is the population.